2020
DOI: 10.1186/s40317-020-00197-w
|View full text |Cite
|
Sign up to set email alerts
|

Seagrass canopies and the performance of acoustic telemetry: implications for the interpretation of fish movements

Abstract: Background: Acoustic telemetry has been used with great success to quantify the movements of marine fishes in open habitats, however research has begun to focus on patterns of movement and habitat usage within more structurally complex habitats. To date, there has been no detailed assessment of the performance of acoustic telemetry within seagrass, which forms a crucial nursery and foraging habitat for many fish species globally. Information on the detection range of acoustic receivers within seagrass is essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 54 publications
4
41
1
Order By: Relevance
“…Previous studies using BPSK or PPM systems working at 180 kHz in freshwater environments showed even larger acoustic ranges of around 200-300 m [23,24], reduced to 80-100 m when applied in the coastal ocean [37]. In comparison, the usual 69 kHz PPM systems used in coastal marine environments usually report an acoustic range between 150 and 300 m [38,39]. Overall, the main advantage of highfrequency systems over systems working at lower frequencies resides in the smaller size of their piezoceramics and the shorter duration of their signals, which allow the production of smaller transmitters and the simultaneous tracking of a larger number of individuals, but in return, present smaller acoustic ranges.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies using BPSK or PPM systems working at 180 kHz in freshwater environments showed even larger acoustic ranges of around 200-300 m [23,24], reduced to 80-100 m when applied in the coastal ocean [37]. In comparison, the usual 69 kHz PPM systems used in coastal marine environments usually report an acoustic range between 150 and 300 m [38,39]. Overall, the main advantage of highfrequency systems over systems working at lower frequencies resides in the smaller size of their piezoceramics and the shorter duration of their signals, which allow the production of smaller transmitters and the simultaneous tracking of a larger number of individuals, but in return, present smaller acoustic ranges.…”
Section: Discussionmentioning
confidence: 94%
“…It has been described that BPSK coding systems are less affected by environmental noise than PPM systems, because the shorter duration of the signals reduces the probability of interferences [24]. It is also known that the presence of complex habitats, such as coral reefs or dense vegetation, lower the detection and positioning efficiency of acoustic telemetry systems [14,39]. The combination between physical factors and the receiver set up also can also affect the acoustic range, for instance, by currents modifying the receiver tilt angle in receivers fixed to ropes or buoys [40].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest turtles in SJB responded little, at least with obvious and/or large-scale movements, to the storm both before and after landfall. Our small sample sizes, paired with limitations of non-GPS capable satellite tags in identifying fine-scale movements 33 and the potential impacts of shallow and rough water on acoustic receiver detections 34 , make it difficult for us to confirm fine-scale changes in behavior. In addition, it is difficult to say if behaviors observed in this study (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The following assumption was made: when no receiver was removed, and thus all receivers were included in the positional analysis, the number of fish positions detected within that set-up was 100% and the triangulated positions were the 'base' fish positions. This provided the possibility to determine two metrics for each APT performance: set-up efficiency and position accuracy [1,15], for each single receiver removal option (i.e. eight or nine for F05 and C05 respectively).…”
Section: Individual Receiver Contribution To Aptsmentioning
confidence: 99%
“…Any factor influencing, or interfering with, speed-of-sound and signal propagation in the water will therefore affect APT performance [13,14]. Habitat-specific features such as vegetation type and density, bottom characteristics and presence of rocks and/or (man-made) obstacles can block signal propagation [15]. Furthermore, natural events like currents and surface waves can influence receiver detection range [12,16] and can even lead to signal propagation interference through receivers getting temporarily buried or even lost [17].…”
Section: Introductionmentioning
confidence: 99%